Tiny magnetic resonance imaging black spot - Presenting an interesting case of internuclear ophthalmoplegia with radioanatomical correlation (Indian Journal of Case Reports, 2018)
Horizontal gaze palsy involves three different entities of similar imaging findings with subtle differences and a prominent difference in the clinical findings. A thorough knowledge of the anatomy of the pathway of horizontal gaze pathways is essential before coming to the correct diagnosis. Here, we report the case of a 42-year-old male patient presented with a history of impaired vision for 1 day. Through this case report, we will revisit these three entities with a brief discussion on the pathways involved in horizontal gaze palsies.